2020
DOI: 10.3892/mmr.2020.11759
|View full text |Cite
|
Sign up to set email alerts
|

miR‑34c‑5p targets Notch1 and suppresses the metastasis and invasion of cervical cancer

Abstract: Micro (mi)RNAs are crucial participants in the progression of cervical cancer (CC). Growing evidence indicates that miRNA (miR)-34c-5p is a pivotal tumor suppressor in numerous types of cancer and its functions in CC require further investigating. The present study demonstrated that there was a decreased level of miR-34c-5p in CC-associated cell lines compared with healthy control samples. It also demonstrated that miR-34c-5p targeted Notch1 and suppressed CC progression. Dual-Luciferase reporter assays verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
(38 reference statements)
1
13
1
Order By: Relevance
“…Yang [30] et aldemonstrated that miR-362 could work as an anti-oncomiR that suppressed proliferation and promoted apoptosis in CC cells via BAP31 and TGFβ/Smad pathway. Wei [31] et al verified that miR-34c-5p targeted Notch 1 and inhibited the metastasis and invasion of CC. It was reported that miR-381 targeted GPR34 to regulate the growth, migration and invasion of human CC cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…Yang [30] et aldemonstrated that miR-362 could work as an anti-oncomiR that suppressed proliferation and promoted apoptosis in CC cells via BAP31 and TGFβ/Smad pathway. Wei [31] et al verified that miR-34c-5p targeted Notch 1 and inhibited the metastasis and invasion of CC. It was reported that miR-381 targeted GPR34 to regulate the growth, migration and invasion of human CC cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA KCNQ1OT1 sponges miR-34c-5p to enhances osteosarcoma progression by ALDOA-enhanced aerobic glycolysis [ 31 ]. miR-34c-5p represses Notch1 and inhibits invasion and metastasis of cervical cancer [ 21 ]. miR-34c-5p regulates paclitaxel-induced apoptosis of lung cancer cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely accepted that miRNAs play pivotal roles in the regulation of cancer development, as well as drug resistance, by directly targeting mRNAs [ 18 20 ]. miR-34c-5p is able to inhibit Notch1 and represses invasion and metastasis in cervical cancer [ 21 ]. SIRT6 targeted by miR-34c-5p contributes to proliferation of colon cancer by JAK2/STAT3 signaling [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the same miRNA may act as a tumor-promoting gene or a tumor suppressor gene in different cancers. For example, miR-34c-5p inhibits the proliferation, migration, and invasion of osteosarcoma cells by targeting FLOT2 (34), and suppresses the metastasis and invasion of cervical cancer by targeting Notch 1 (35). However, miR-34c-5p can also promote colon cancer cell proliferation by targeting SIRT6 via activation of the JAK2/STAT3 signaling pathway (36).…”
Section: Discussionmentioning
confidence: 99%